Dynamic keyhole behavior and keyhole instability in high power fiber laser welding of stainless steel. (June 2019) - Zhang, Dabin; Wang, Meng; Shu, Chengsong; Zhang, Yunfei; Wu, Dongsheng; Ye, Youxiong
Highlights: The dynamic keyhole behavior in high power fiber laser welding is clearly observed. A three-dimensional numerical model is developed to study the keyhole behavior. Two mechanisms are proposed to be responsible for the keyhole induced bubble formation. Abstract: A three-dimensional numerical model, considering the real-time multiple reflections of a laser beam, adiabatic bubble model and shear stress, was developed to study the dynamic keyhole behavior and keyhole instability in fiber laser welding of stainless steel. The inner dynamic keyhole behavior and weld defect formation were directly observed in a high resolution assisted by transparent glass. The numerical and experimental results showed that the keyhole width reached the quasi-steady state earlier than the keyhole depth did during fiber laser welding of stainless steel. Due to the large recoil pressure at rear keyhole wall caused by the irradiation of laser energy reflected by the bulge at the front keyhole wall, the rear keyhole wall was severely deformed at keyhole bottom and keyhole middle. The rear keyhole wall was collapsed due to the high surface tension pressure and hydrostatic pressure. The whole keyhole collapse was attributable to the capillary instability of the keyhole associated with large depth/width ratio and the strong flow of the bulges at the keyhole wall. When the laser power was increased, the keyhole depth/width ratio was increased, so the keyhole was more capillary instable. The average inclined angle of the front keyhole wall was decreased.